A RBI Mapping Geographic Information System in Pangkep Regency Using ArcGis Online - Ramlah, Ramlah; Ramadhan, Muhammad Alif; H., Muhammad Rizal (International Journal of Informatics, Economics, Management and Science; Vol 3 No 2 (2024): IJIEMS (August 2024)DO - 10.52362/ijiems.v3i2.1560, 2024)
The Indonesian Medan Map (RBI) is  a topographic map that displays several natural and man-made elements in the territory of the Republic of Indonesia, especially in Pangkep Regency. The purpose of this study is to map sixteen RBI objects, namely Hospitals, Education, Industry, Health Centers, PLN Offices, Package Delivery Offices, Worship Facilities, Government, Ports, Post Offices, Gas Stations, Rivers, Dams, Roads, Irrigation, and Settlements. Use the ArcGIS Online app. This mapping is useful for providing information about the spatial data of objects and topographic maps. The method used is a survey by determining the coordinate points of each object. Furthermore, coordinate points are used as data input in ArcGIS applications. Primary data collection is carried out by direct observation of objects or places. Secondary data collection includes Quickbird Citra Pangkep Regency, as well as the Indonesian Medan Map (RBI). Data analysis was carried out in a descriptive manner. Based on the results of object mapping in Pangkep Regency, there are sixteen RBI objects, including: three health service objects, one education object, four transportation objects, five construction work service objects, one government object, one housing object and one worship object object. Sixteen RBI objects are spread throughout Pangkep district.